On the growth of a periodic meromorphic function - Tėvelis, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Тевялис. О росте периодических мероморфных функций V. Tėvelis. Apie periodinių meromorfinių funkcijų augimą